Research on the thermal comfort of the elderly in rural areas of cold climate, China. Issue 5 (3rd September 2022) - Yuan, Jingyu; Cong, Yuting; Yao, Sheng; Dai, Chenrui; Li, Yitong
ABSTRACT: At present, the thermal comfort evaluation index has not been differentiated for different types of people, and the indoor thermal environment of the residences in rural areas of cold climate, China, urgently need attention. In this study, indoor living environment of rural residences in Hebei and Tianjin were measured to obtain typical residential forms, building thermal parameters and thermal comfort parameters of the elderly. At the same time, 152 elderly people were investigated by questionnaire to obtain the subjective evaluation such as thermal sensation. In addition, the optimization suggestions of plane structure, building envelope and window to wall ratio were put forward through software simulation. The results show that the thermal neutral temperature of the rural elderly people in cold zone is 16.74°C, and they are more sensitive to the temperature below 15.67°C and more slowly to the temperature above 15.67°C. The recommended thickness of wall insulation layer is 80–100 mm, and that of roof insulation layer is 60–80 mm. Double layer glass should be used. Wood window frame has better thermal insulation effect than aluminium frame, and the recommended window to wall ratio is 0.28.